Obstruction of ventricular Ca2+‐dependent arrhythmogenicity by inositol 1, 4, 5‐trisphosphate‐triggered sarcoplasmic reticulum Ca2+ release. (7th August 2018) - Blanch i Salvador, Joaquim; Egger, Marcel
Abstract : Key points: Augmented inositol 1, 4, 5‐trisphosphate (IP3 ) receptor (IP3 R2) expression has been linked to a variety of cardiac pathologies. Although cardiac IP3 R2 function has been in the focus of research for some time, a detailed understanding of its potential role in ventricular myocyte excitation–contraction coupling under pathophysiological conditions remains elusive. The present study focuses on mechanisms of IP3 R2‐mediated sarcoplasmic reticulum (SR)‐Ca 2+ release in ventricular excitation–contraction coupling under IP3 R2‐overexpressing conditions by studying intracellular Ca 2+ events. We report that, upon IP3 R2 overexpression in ventricular myocytes, IP3 ‐induced Ca 2+ release (IP3 ICR) modulates the SR‐Ca 2+ content via "eventless" SR‐Ca 2+ release, affecting the global SR‐Ca 2+ leak. Thus, IP3 R2 activation could act as a SR‐Ca 2+ gateway mechanism to escape ominous SR‐Ca 2+ overload. Our approach unmasks a so far unrecognized mechanism by which "eventless" IP3 ICR plays a protective role against ventricular Ca 2+ ‐dependent arrhythmogenicity. Abstract: Augmented inositol 1, 4, 5‐trisphosphate (IP3 ) receptor (IP3 R2) function has been linked to a variety of cardiac pathologies including cardiac arrhythmias. The functional role of IP3 ‐induced Ca 2+ release (IP3 ICR) within ventricular excitation–contraction coupling (ECC) remains elusive. As part of pathophysiological cellular remodelling, IP3 R2s are overexpressed and have been repeatedly linked to enhanced Ca 2+ ‐dependent arrhythmogenicity. In this study we test the hypothesis that an opposite scenario might be plausible in which IP3 ICR is part of an ECC protecting mechanism, resulting in a Ca 2+ ‐dependent anti‐arrhythmogenic response on the cellular scale. IP3 R2 activation was triggered via endothelin‐1 or IP3 ‐salt application in single ventricular myocytes from a cardiac‐specific IP3 R type 2 overexpressing mouse model. Upon IP3 R2 overexpression, IP3 R activation reduced Ca 2+ ‐wave occurrence (46 vs . 21.72%; P  < 0.001) while its block increased SR‐Ca 2+ content (∼29.4% 2‐aminoethoxydiphenyl borate, ∼16.4% xestospongin C; P  < 0.001), suggesting an active role of IP3 ICR in SR‐Ca 2+ content regulation and anti‐arrhythmogenic function. Pharmacological separation of ryanodine receptor RyR2 and IP3 R2 functions and two‐dimensional Ca 2+ event analysis failed to identify local IP3 ICR events (Ca 2+ puffs). SR‐Ca 2+ leak measurements revealed that under pathophysiological conditions, "eventless" SR‐Ca 2+ efflux via enhanced IP3 ICR maintains the SR‐Ca 2+ content below Ca 2+ spark threshold, preventing aberrant SR‐Ca 2+ release and resulting in a protective mechanism against SR‐Ca 2+ overload and arrhythmias. Our results support a so far unrecognized modulatory mechanism in ventricular myocytes working in an anti‐arrhythmogenic fashion. Key points: Augmented inositol 1, 4, 5‐trisphosphate (IP3 ) receptor (IP3 R2) expression has been linked to a variety of cardiac pathologies. Although cardiac IP3 R2 function has been in the focus of research for some time, a detailed understanding of its potential role in ventricular myocyte excitation–contraction coupling under pathophysiological conditions remains elusive. The present study focuses on mechanisms of IP3 R2‐mediated sarcoplasmic reticulum (SR)‐Ca 2+ release in ventricular excitation–contraction coupling under IP3 R2‐overexpressing conditions by studying intracellular Ca 2+ events. We report that, upon IP3 R2 overexpression in ventricular myocytes, IP3 ‐induced Ca 2+ release (IP3 ICR) modulates the SR‐Ca 2+ content via "eventless" SR‐Ca 2+ release, affecting the global SR‐Ca 2+ leak. Thus, IP3 R2 activation could act as a SR‐Ca 2+ gateway mechanism to escape ominous SR‐Ca 2+ overload. Our approach unmasks a so far unrecognized mechanism by which "eventless" IP3 ICR plays a protective role against ventricular Ca 2+ ‐dependent arrhythmogenicity.